Implementation of a web service with SAP B1 DI API for quotation management in a company in the industrial sector - Sierra-Liñan, Fernando; Larrea-García, Kevin (LACCEI, 2025)
In the industrial sector, many organizations tend to look for optimal technological solutions for their processes; however, over time some of these solutions become obsolete. In this sense, companies have chosen to improve the business systems they have in their possession, through web services or systems hosted in the cloud. Therefore, the research aimed to improve the quotation management process with the implementation of a web service using the SAP Business One DI API. The research is of an applied type, with a quantitative approach, experimental design with a pre-experimental degree and explanatory level. The sample was 10 sales employees of an industrial organization, being non-probabilistic for convenience. The agile development methodology SCRUM was used, with C# and Java as programming languages. As for the database, HANA was used for compatibility with SAP. Likewise, the SAP DI API was used for secure connections and methods to the ERP. The results achieved after the implementation of the web service were the following: The increase in the number of quotations prepared by 36.62%, the reduction in the time taken to prepare quotations by 49.11%, the reduction in the costs of quotation management by 65.63% and the improvement in the satisfaction of quotation management with the implementation of the web service, where 80% of employees are very satisfied.